Brodalumab for the treatment of moderate‐to‐severe plaque‐type psoriasis: a real‐life, retrospective 24‐week experience. (13th October 2020) - Fargnoli, M.C.; Esposito, M.; Dapavo, P.; Parodi, A.; Rossi, M.; Tiberio, R.; Dastoli, S.; Offidani, A.M.; Argenziano, G.; Gisondi, P.; Lo Schiavo, A.; Loconsole, F.; et al.
Abstract: Background: Brodalumab was efficacious and safe in moderate‐to‐severe plaque‐type psoriasis in the AMAGINE trials; published reports under real‐life conditions are limited. Objectives: To evaluate the effectiveness and safety of brodalumab in patients with moderate‐to‐severe plaque‐type psoriasis in a real‐world setting. Methods: This observational, retrospective study enrolled adult patients (≥18 years) with moderate‐to‐severe plaque‐type psoriasis who underwent 24 weeks of treatment with brodalumab at 17 Italian dermatological centres. Baseline data included demographics, comorbidities, age of onset and duration of psoriasis and previous treatments. Psoriasis Area and Severity Index (PASI), Physician Global Assessment (PGA), static PGA of Genitalia, Dermatology Life Quality Index and patient satisfaction were assessed at weeks 0, 4, 12 and 24; adverse events were recorded. Results: Seventy‐eight patients (mean age 47.9 years, 71.8% male, average disease duration 16.8 years) were enrolled. A rapid and significant reduction in mean PASI score was observed after 4 weeks of treatment, decreasing further at weeks 12 and 24 (all P  < 0.0001 vs. baseline). A higher number of cardiometabolic comorbidities and previous therapies were negatively associated with the achievement of PASI 90 at all assessments. Brodalumab was effective in bio‐experienced patients, including those who had failed on anti‐interleukin (IL)‐17 therapies. Quality of life and patient satisfaction increased significantly during treatment ( P  < 0.0001 and P  < 0.01 vs. baseline, respectively). Treatment was interrupted in 9 (11.5%) patients due to adverse events ( n  = 4), lack of efficacy ( n  = 3), lost to follow‐up ( n  = 1) and surgical procedure ( n  = 1). Conclusions: Brodalumab is effective and safe in the treatment of moderate‐to‐severe psoriasis in a real‐world setting, including in patients with failure to anti‐IL17 therapies.